Information density–based energy-limited capacity of ad hoc networks - Zhiqing Wei; Ziyu Wang; Xin Yuan; Huici Wu; Zhiyong Feng (International Journal of Distributed Sensor Networks)
In this article, the inhomogeneous energy consumption is characterized by the concept of information density, which is defined as the number of bits per unit time passing through a specific region. With information density, it is possible to derive the energy consumption of each region and determine the energy configuration scheme to maximize the network lifetime. The information density of pure ad hoc network and hybrid ad hoc network is derived. It is discovered that the information density of pure ad hoc network is inhomogeneous and the information density of hybrid ad hoc network is homogeneous, except for the regions near the edge of the entire area. With information density, the energy-limited capacity of pure and hybrid ad hoc networks is derived. The information density introduced in this article provides more insights into the information transfer of ad hoc networks, which may be applied in the energy configuration of ad hoc networks.